Experimental campaign on structural aluminium alloys under monotonic and cyclic loading. (1st May 2023) - Pisapia, Alessandro; Nastri, Elide; Piluso, Vincenzo; Formisano, Antonio; Massimo Mazzolani, Federico
Highlights: Experimental tests have been performed on 57 extruded aluminium bars. One and two stages Ramberg-Osgood models have been provided for each tested aluminium alloy. The low cycle fatigue curves have been obtained for 6060, 6082 and 7075 alloys. Ductility and dissipation have been evaluated in the cyclic tests. The skeleton curves are derived for each aluminium alloys by means of the incremental cyclic tests. Abstract: In the present paper an extensive experimental campaign is carried out on 5000, 6000 and 7000 aluminium series through monotonic and cyclic tests. The research is part of a collaboration between the Universities of Salerno and Naples "Federico II" involved for several decades in the development of the Eurocode recommendation regarding the aluminium alloys for structural purposes. The experimental program is composed of 3 monotonic experiments for each aluminium alloy, 29 low-cycle fatigue tests for 6060, 6082 and 7075 alloys and 10 incremental cyclic tests under different loading cycles for all tested alloys. The main purpose of this campaign is the characterization of such alloys not only in terms of the well-known stress–strain curve while in terms of low cycle fatigue, cyclic hardening, dissipated energy and plastic fracture, to achieve more information about the non linear behaviour which can be exhibited, as an example, under seismic loading. In fact, since now, the largest part of the research has been mainly focused on the behaviour of such materials under a large number of cycles in elastic range thus neglecting the potential benefits in exploiting the large dissipative capacity of such alloys. Moreover, the collected information could be of fundamental importance in the framework of the revision of the new Eurocode 8 which presents, for the first time, a section devoted to the seismic design of structures made of aluminium alloys. The accurate knowledge of the random material variability and cyclic hardening could be helpful for the setting up of the coefficients to be used for the application of the hierarchy criteria.